A new nationalist Europe under Hitler : concepts of Europe and transnational networks in the National Socialist sphere of influence, 1933-1945 - Dafinger, Johannes Herausgeber; Pohl, Dieter, 1964- 1964- Herausgeber (Routledge studies in Second World War history, 2019)
"Nazis, fascists and völkisch conservatives in different European countries not only cooperated internationally in the fields of culture, science, economy, and persecution of Jews, but also developed ideas for a racist and ethno-nationalist Europe under Hitler. The present volume attempts to combine an analysis of Nazi Germany's transnational relations with an evaluation of the discourse that accompanied these relations"...